INTEGRASI MEDIA VISUAL DAN DIGITAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Nelmawati Nelmawati; Novia Adila; Ahmad Kailani; Ismail Syakban (STKIP Pesisir Selatan, 2025)
Objective: The integration of visual and digital media in Islamic Religious Education (IRE) learning at the elementary school level is an important effort to improve the quality of the learning process and student engagement. This study aims to describe the practice of integrating visual and digital media in IRE learning and to identify the challenges encountered in its implementation at SD 10 Tarung-Tarung Utara. This research employed a qualitative approach, with data collected through classroom observations, interviews with IRE teachers and school administrators, and documentation analysis of instructional planning materials. The findings indicate that the use of visual and digital media in IRE learning has not been optimally integrated. Teachers still tend to rely on conventional teaching methods with limited use of instructional media. Digital media are used incidentally and are not systematically planned within lesson designs. The main challenges include limited supporting facilities, insufficient teacher competence in managing digital media, and the absence of school policies that encourage sustainable media integration. These findings highlight the need for strengthening teacher competencies and institutional support to ensure more effective integration of visual and digital media in elementary-level IRE learning.